PTU-071 Impact of body mass index (BMI) upon anti-tnf trough and anti-drug antibody levels. (22nd June 2015) - Bond, A; sager, K; Phillips, S; Asher, R; Jackson, R; Kneebone, A; Martin, K; Subramanian, S
Abstract : Introduction: The anti-tumour necrosis factor (TNF) agents, infliximab and adalimumab, are effective in treating inflammatory bowel diseases (IBD). Response is better in patients with detectable levels of circulating drug prior to the next administration (trough level). Some patients fail to respond to these drugs initially or lose response over time. Factors which influence loss of response are poorly defined but body mass index (BMI), prior surgery and smoking status have been reported to influence outcomes. In particular, BMI adversely affect outcomes with both infliximab and adalimumab, but the relationship of BMI to trough levels has not been reported previously. Method: We conducted a single centre prospective cross-sectional study. All IBD patients treated with infliximab or adalimumab were eligible. Trough levels and anti-drug antibodies were obtained concurrently with routine clinical data, clinical markers of disease activity, faecal calprotectin (FC), C-reactive protein (CRP) and BMI. Variables including BMI that may predict trough levels and anti-drug antibodies were then assessed. Therapeutic infliximab was defined as trough level >2 mcg/ml (need units and adalimumab as >5.5 microgram/ml. Results: 87 patients were included in the study; 69 had CD (44 IFX, 25 ADA) and 18 had UC (9 each on IFX and ADA). Of the total cohort, 12 had undetectable trough levels (<0.1) and 22 had supra-therapeutic levels (>8). A higher percentage of patients with undetectable trough levels were on infliximab (92% vs 8%, p < 0.01). Supra-therapeutic levels were noted in 55% and 45% of infliximab and adalimumab patients respectively. In the infliximab group, the median BMI was 24.9 (range 17.23–42.28), and 26 had aBMI >25 (49%). For adalimumab the median BMI was 22.92 (range 16.14–37.64), and 13 had a BMI >25 (38%). Those with sub-therapeutic trough levels had a higher BMI, which is most prominent in the adalimumab group. Patients with sub-therapeutic levels of infliximab had a median BMI of 25.3 (IQR: 22.6–30.5) compared to those with therapeutic levels 23.8 (IQR: 19.9–29.6). For adalimumab the median BMI was 22.8 (IQR: 20.5–25.6) in therapeutic and 27.4 (IQR: 21.9–32.9) in the sub-therapeutic group but this did not reach statistical significance. Conclusion: There does appear to be a correlation between BMI and trough levels, particularly in patients receiving adalimumab. Therefore trough level measurement and dose adjustment, particularly in those taking adalimumab with a BMI >25, should be considered to optimise therapy and clinical outcomes. Disclosure of interest: None Declared.